All in: Ideological lexicon of online poker - Peláez Torres, Luis Carlos (2021)
This paper is a semantic-lexicographic description of the gambling game known as poker in online mode. The objective of the research is to provide an onomasiological lexicon of the terms used by users of online poker applications based on the theory of semantic fields. In this sense, we use a terminological methodology that consists of grouping lexical entries into hyperonymic and holonymic categories, so that we start from a concept to arrive at the hyponymic and meronymic term, respectively. The analysis was performed on the basis of lexical samples taken from online poker rooms, from video tutorials published by game broadcasters and enthusiasts, as well as from bibliographic sources collecting them (manuals and glossaries). For this purpose, a corpus is compiled, the terms are conceptually organized and defined according to seven semantic fields: bet, expression, money, move, player, hand, program and turn, so that they can be arranged in a hypertextual computer support.